Exploring lipidome mediated inflammatory pathways in acute pancreatitis using mendelian randomization - Wenbin Liu; Song Yang; Yuhan Li; Dava Tenzing; Ruizi Shi; Yang Jiang; Hao Deng; Enqiang Mao; Ying Chen; Yihui Wang (Scientific Reports)
Abstract Acute pancreatitis (AP) is a severe gastrointestinal condition with an increasing incidence of hyperlipidemic etiology. The investigation employed a two-sample, bidirectional Mendelian randomization method to investigate potential causal relationship between lipidome profiles, inflammatory mediators, and AP. Exploration of genetic variants across the genome in a study population of 10,630 AP cases and 844,679 non-AP individuals revealed multiple lipidome entities significantly associated with AP risk. The study identified 23 lipid species with unidirectional causal effects on AP after accounting for heterogeneity, pleiotropy, and potential reverse causation. Additionally, five inflammatory factors (CD5, IL-13, MMP-1, STAMBP, TNFRSF9) showed significant potential causal relationship with AP. Further analysis elucidated the intricate interplay between specific lipid species and inflammatory mediators in influencing AP incidence. Notably, Sterol ester (27:1/20:4) and several phosphatidylcholine species, including PC (17:0_20:4), PC (18:0_20:4), PC (18:0_20:5), and PC (O-18:2_20:4), were negatively associated with AP risk. This protective effect was partially mediated through decreased levels of inflammatory markers, particularly STAMBP and MMP-1. The study found that these phosphatidylcholines and sterol esters significantly reduced the levels of these pro-inflammatory factors, thereby potentially mitigating AP risk. Conversely, Phosphatidylinositol (16:0_18:1) demonstrated a positive association with AP risk. This detrimental effect was partially mediated by increased levels of MMP-1 and STAMBP, suggesting a pro-inflammatory mechanism. The study provides evidence that this specific phosphatidylinositol species may exacerbate AP risk by promoting inflammatory pathways. These findings elucidate the complex interplay between lipid metabolites, inflammation, and AP pathogenesis, potentially informing novel therapeutic strategies. The study highlights the utility of Mendelian randomization in uncovering potential causal relationship in AP. It underscores the requirement for further study into the molecular mechanisms underlying lipid-mediated inflammation in AP, particularly the roles of phosphatidylcholines and sterol esters in modulating inflammatory responses. Further studies are warranted to confirm our observations in laboratory models and assess their translational value in developing AP preventive and therapeutic strategies.